Crianças haitianas na educação infantil em Sorocaba - SP (2011-2019) - Lorzing, Renata de Moura Santos (Universidade Federal de São Carlos, 2021)
International migrations is a subject discussed all over the world in the most diverse areas of knowledge, including Education. This research aims to understand and understand the processes of welcoming Haitian children in public preschools in the city of Sorocaba-SP, Brazil. We also seek to identify and analyze the role that interactions and games – guiding principles of Early Childhood Education, according to the National Curriculum Guidelines for Early Childhood Education (Diretrizes Curriculares Nacionais da Educação Infantil - DCNEIs) – can play in this embracement. It also intends to raise available references and deepen readings and studies on the relationship between migration and education. It also seeks, through interviews with teachers, to identify the main challenges encountered in the experiences with Haitian children, who, in addition to being migrants, are black. In addition, this academic thesis aims to analyze official documents of the Department of Education in order to draw an overview of migrant children enrolled in the public network of early childhood education in Sorocaba. We base our studies on migration on Katia Norões (2016, 2018, 2020), Abdelmalek Sayad (1998), Ethel Volfzon Kosminsky (2000), Demartini (2011, 2012, 2017). The methodology is based on qualitative research, with literature review and analysis of interviews with teachers. The survey's findings indicate that the number of Haitian children enrolled in the municipal network of Sorocaba is large and that the challenges faced by teachers are also large. Among these challenges are the lack of public policies aimed at migrant children and communication with children and their families (language).
Haitian children in early childhood education in Sorocaba - SP (2011-2019)
Keywords: Educação infantil; Crianças haitianas; Migração; Acolhimento; Early childhood education; Haitian children; Migration; Welcoming; CIENCIAS HUMANAS::EDUCACAO